Analisis Tingkat Kemampuan Komunikasi Matematis Siswa pada Pembelajaran Daring - Wahyuni, Lena; Wulantina, Endah (Tapis: Jurnal Penelitian Ilmiah, 2022)
This study aims to analyze the level of mathematical communication ability of junior high school students in online learning. The research method used is descriptive quantitative using a mathematical communication ability test instrument. Indicators of mathematical communication ability that must be achieved are 1) Converting real objects, pictures, and diagrams into mathematical ideas; 2) Expressing mathematical ideas through oral, written, and visually described; 3) Analyzing and evaluating mathematical ideas both orally and in writing; 4) Modeling mathematical situations or problems using language terms or mathematical symbols, and their structures; 5) Explaining answers to problems systematically. The subjects of this study were seventh-grade students of SMP N 1 Seputih Raman. The result of this research is the level of students' mathematical communication skills in online learning is in a low category. Students with a high level of mathematical communication ability (3.64%) are able to meet the five indicators of mathematical communication skills. Students with a moderate level of mathematical communication ability (15.94%) were not able to fulfill the first and second indicators. Students with low mathematical communication ability (80.43%) cannot fulfill the five indicators.